Differences in neuroanatomy and functional connectivity between motor subtypes of Parkinson’s disease - Zheng, Jin Hua; Sun, Wen Hua; Ma, Jian Jun; Wang, Zhi Dong; Chang, Qing Qing; Dong, Lin Rui; Shi, Xiao Xue; Li, Ming Jian; Gu, Qi; Chen, Si Yuan; Li, Dong Sheng (Frontiers in Neuroscience, 2022)
Background The “postural instability/gait difficulty” (PIGD) and “tremor-dominant” (TD) motor subtypes of Parkinson’s disease (PD) differ in their clinical manifestations. The neurological basis of these differences is unclear. Methods We performed voxel-based morphometric analysis and measured amplitudes of low-frequency fluctuation (ALFF) on 87 PIGD patients and 51 TD patients. We complemented this neuroanatomical comparison with seed-to-voxel analysis to explore differences in functional connectivity. Results The PIGD group showed significantly smaller gray matter volume in the medial frontal gyrus (mainly on the right side) than the TD group. Across all patients, gray matter volume in the medial frontal gyrus correlated negatively with severity of PIGD symptoms after controlling for age (r = −0.250, p = 0.003), but this correlation was not observed in separate analyses of only PIGD or TD patients. The PIGD group showed greater functional connectivity of the right superior frontal gyrus with the left lingual gyrus, right lateral occipital cortex, and right lingual gyrus. ALFF did not differ significantly between the two groups. Conclusion Postural instability/gait difficulty may be associated with smaller gray matter volume in medial frontal gyrus than TD, as well as with greater functional connectivity between the right superior frontal gyrus and occipital cortex. These results may help explain the clinical differences between the two motor subtypes of PD.